The modified Yi qi decoction protects cardiac ischemia-reperfusion induced injury in rats - Xiao Yu; Xiao-Dong Zhao; Rong-Qi Bao; Jia-Yu Yu; Guo-Xing Zhang; Jing-Wei Chen (BMC, 2017)
Abstract Background To investigate the effects and involved mechanisms of the modified Yi Qi decoction (MYQ) in cardiac ischemia-reperfusion (IR) induced injury. Methods Male Sprague-Dawley rats were subjected to a 30-min coronary arterial occlusion followed by reperfusion, low or high dose decoction of MYQ was administrated orally for 1 week or 1 month. Results Both in 1 week and 1 month IR rat groups, cardiac function indexes were significantly impaired compared with sham group rats, accompanied with higher ratio of infarct size to risk size, decreased expressions of sodium calcium exchanger (NCX1) and sarcoplasmic reticulum Ca2+-ATPase (Serca2a), and different expressions of autophagic proteins, Beclin-1 and LC3. Treatment with MYQ (low or high dose) for 1 week showed no marked beneficial effects on cardiac function and cardiac injury (ratio of infarct size to risk size), although expressions of anti-apoptotic protein, Bcl-2, NCX1 and Serca2a were increased. Treatment with MYQ (low or high dose) for 1 month showed significantly improved effects on cardiac function and cardiac injury (ratio of infarct size to risk size), accompanied with increase of Bcl-2, NCX1 and Serca2a expressions, and decrease of Bax (a pro-apoptotic protein) and Beclin-1 expressions. Conclusions The results show that MYQ have potential therapeutic effects on IR-induced cardiac injury, which may be through regulation of apoptotic proteins, cytosolic Ca2+ handling proteins and autophagic proteins signal pathways.